Sometimes two arms are enough—an unusual life-stage in brittle stars (Echinodermata: Ophiuroidea) - Stöhr, Sabine; Alme, Øydis (Zootaxa, 2015)
Off West Africa (Angola–Morocco), benthos samples were collected in the years 2005–2012. These contained 124 specimens of brittle stars with two long arms and three extremely short or absent arms and an elongated, narrow disc. These unusual brittle stars, as well as 33 specimens with five fully developed arms, were identified as Amphiura ungulata. The specimens with unequal arms were juvenile stages, whereas adults had five equal arms. The large number of specimens with unequal arms suggests that this condition is not the result of damage and regeneration, but a normal growth pattern in this species. This study documents the morphology by SEM, amends the species description, and discusses possible explanations for the evolution of this condition. Although brittle star species with unequal arm growth have been reported, this is an extreme case that was unknown before this study.